Tofu Wastewater Treatment Using Biocoagulant Moringa Seed Powder (Moringa Oleifera L) - Nora, Fitrisia; Marhadi; Adriansyah, Endi; Suzana, Asih; Pramono, M. Sidik; Sufra, Rifqi; Syaiful, M. (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
Indonesia has various types of vegetation which are used as natural coagulants or biocoagulants. Coagulants can be divided into chemical coagulants and natural coagulants (biocoagulants). Biocoagulants are more environmentally friendly and can be obtained from natural ingredients, both animals and plants, one of which is Moringa seeds. Moringa seeds or with the Latin name Moringa oleifera are a type of plant from the Moringaceae family. From several previous studies, Moringa seeds were used as a more economical and environmentally friendly wastewater treatment method. Moringa seed biocoagulant in powder form is made from ripe and old moringa seeds and contains less than 10% water. Moringa seed biocoagulant contains 4αL-rhamnosyloxy-benzylisothiocyanate and is a determinant of coagulation effectiveness. This active substance is able to absorb pollutants in waste water. This research aims to treat tofu waste with moringa seed biocoagulant in reducing pollutant parameters, namely TSS (Total Suspended Solid) and COD (Chemical Oxygen Demand). Results of the removal of pollutants from moringa seed powder biocoagulant in tofu waste water the efficiency value obtained for each TSS parameter, and the COD for the TSS parameter is 54.4%. and for the COD parameter of 14.6%, it can be concluded that the efficiency value for each parameter still does not meet the effectiveness value.